Male working carers: a qualitative analysis of males involved in caring alongside full-time paid work. (1st August 2019) - Maynard, Kevin; Williams, Allison; Ilagan, Chloe
Abstract : Given ageing demographics, the need for carers will increase and studies suggest that men are nearly as likely as women to become carers. The purpose of this study is to understand the specific challenges that male working carers experience with regard to social life and paid work. Participant recruitment was conducted through local carer support groups and male-dominated workplaces. Using a semi-structured format, 15 interviews were conducted. Findings suggest a variety of themes, including caring characteristics, the effects of caring, support systems and coping strategies. Our results indicate that the male working carer population faces specific challenges in the workplace and social settings.